Tectonic units of the Alpine collision zone between Eastern Alps and western Turkey - Schmid, Stefan M.; Fügenschuh, Bernhard; Kounov, Alexandre; Maţenco, Liviu; Nievergelt, Peter; Oberhänsli, Roland; Pleuger, Jan; Schefer, Senecio; Schuster, Ralf; Tomljenović, Bruno; Ustaszewski, Kamil; van Hinsbergen, Douwe J.J. (Gondwana research, 2020)
We present a map that correlates tectonic units between Alps and western Turkey accompanied by a text providing access to literature data, explaining the concepts used for defining the mapped tectonic units, and first-order paleogeographic inferences. Along-strike similarities and differences of the Alpine-Eastern Mediterranean orogenic system are discussed. The map allows (1) for superimposing additional information, such as e.g., post-tectonic sedimentary basins, manifestations of magmatic activity, onto a coherent tectonic framework and (2) for outlining the major features of the Alpine-Eastern Mediterranean orogen. Dinarides-Hellenides, Anatolides and Taurides are orogens of opposite subduction polarity and direction of major transport with respect to Alps and Carpathians, and polarity switches across the Mid-Hungarian fault zone. The Dinarides-Hellenides-Taurides (and Apennines) consist of nappes detached from the Greater Adriatic continental margin during Cretaceous and Cenozoic orogeny. Internal units form composite nappes that passively carry ophiolites obducted in the latest Jurassic–earliest Cretaceous or during the Late Cretaceous on top of the Greater Adriatic margin successions. The ophiolites on top of composite nappes do not represent oceanic sutures zones, but root in the suture zones of Neotethys that formed after obduction. Suturing between Greater Adria and the northern and eastern Neotethys margin occupied by the Tisza and Dacia mega-units and the Pontides occurred in the latest Cretaceous along the Sava-İzmir-Ankara-Erzincan suture zones. The Rhodopian orogen is interpreted as a deep-crustal nappe stack formed in tandem with the Carpatho-Balkanides fold-thrust belt, now exposed in a giant core complex exhumed in late Eocene to Miocene times from below the Carpatho-Balkan orogen and the Circum-Rhodope unit. Its tectonic position is similar to that of the Sakarya unit of the Pontides. We infer that the Rhodope nappe stack formed due to north-directed thrusting. Both Rhodopes and Pontides are suspected to preserve the westernmost relics of the suture zone of Paleotethys. [Display omitted] •Tectonic map correlates tectonic units between Alps and western Turkey.•Profiles visualize architecture of Alpine-eastern Mediterranean orogens.•Review provides overview of Alpine-type orogens across national boundaries.